Perceptions of research experience during internal medicine training: insights from a national survey - Laith Alhuneafat; Randa Mahasneh; Nada Alrifai; Jillian S. Catalanotti; Gopal Yadavalli; Anastasios Kapetanos (Annals of Medicine, 2025)
Background There is limited insights into how internal medicine (IM) residents perceive research. This study aimed to assess residents’ perceptions across five domains: well-being, research competence, research support, effect on training, and research quality.Methods In 2022, a survey instrument was developed to assess residents’ perceptions of research across five domains. All IM programs listed in Fellowship and Residency Electronic Interactive Database (FREIDA) were contacted by email, and residents were invited to participate.Results A total of 530 residents from 67 IM programs completed our survey. Just over 80% of respondents had participated in research during residency. Residents were dissatisfied with research opportunities and infrastructure but viewed research funding more positively. Negative views were held regarding the impact of publication pressure on well-being and the quality of research produced. Publication pressure was perceived to compromise clinical work and limit career paths. Some residents acknowledged that research enriched their training. Residents who had already matched into a fellowship program reported higher research competency and better impressions of the impact of research on their medical training compared to those who had not yet or did not plan to match into a fellowship. Residents who planned to prioritize research in their future careers held positive perceptions of research across multiple domains.Conclusions This study provides valuable insights into the impact of publication pressure on IM residents. The findings suggest a need to realign expectations for research productivity or target interventions to better support research for all residents, regardless of track or career goals.